Economic situation in North Africa - Nurseitova, L. (Journal of Oriental Studies, 2016)
North Africa as an economic region has always attracted the attention of specialists in various fields of knowledge from around the world. Designated region has always remained in the spotlight as a dynamic and creative Arabic Centre. Economic of the North Africa for many years distinguished specificfeatures and unique way of development. The biggest key point is of course peace in Middle East which will lead to better unification of Arab states. Peace will bring more stable economical activities with other nations. In this article the author considers modern economic development of North Africa.